Impact of Instagram in the influence on esthetic perception in silhouettes through eye tracking and questionnaire (Research, Society and Development, 2022)
This study evaluated the influence of the use of Instagram in the esthetic of silhouettes of individuals who underwent orthognathic surgery and rhinoplasty of four different models separated as preoperative, after orthognathic surgery, and after orthognathic rhinoplasty were standardized and edited using Photoshop. OGAMA software and EyeTribe hardware were used for eye tracking. The Qualtrics platform was used to apply the Brief Symptoms Inventory (BSI) questionnaires to assess psychological statuses and use of social media and to evaluate the attractiveness of each image through the visual analog scale (VAS). ANOVA, Kruskal–Wallis, and Pearson's correlation tests were used. Statistically significant differences for time to the first fixation in the lower third, and middle third for attractiveness were observed (p < 0.05). The VAS results were more attractive after orthognathic surgery and rhinoplasty. Pearson's correlation was performed between time spent on Instagram and VAS (p < 0.0001, r = -0.212); individuals who reported spending more time on Instagram gave lower attractiveness scores. In addition, VAS showed significance in relation to BSI global indices (general severity index [p = 0.044, r = -0.078], positive symptom total [p = 0.024, r = -0.08] and positive symptom distress index [p = 0.025, r = -0.08]), suggesting that individuals who scored better tended to assign higher scores to attractiveness. Individuals who reported spending more time on Instagram tended to rate the silhouettes’ attractiveness with lower scores, and individuals who spent more time on Instagram displayed a higher average level of distress.